Chronic Kidney Disease Awareness and Longitudinal Health Outcomes: Results from the REasons for Geographic And Racial Differences in Stroke Study - Tummalapalli, Sri Lekha; Vittinghoff, Eric; Crews, Deidra C; Cushman, Mary; Gutiérrez, Orlando M; Judd, Suzanne E; Kramer, Holly J; Peralta, Carmen A; Tuot, Delphine S; Shlipak, Michael G; Estrella, Michelle M (American journal of nephrology, 2020)
The majority of people with chronic kidney disease (CKD) are unaware of their kidney disease. Assessing the clinical significance of increasing CKD awareness has critical public health and healthcare delivery implications. Whether CKD awareness among persons with CKD is associated with longitudinal health behaviors, disease management, and health outcomes is unknown. We analyzed data from participants with CKD in the REasons for Geographic And Racial Differences in Stroke study, a national, longitudinal, population-based cohort. Our predictor was participant CKD awareness. Outcomes were (1) health behaviors (smoking avoidance, exercise, and nonsteroidal anti-inflammatory drug use); (2) CKD management indicators (angiotensin-converting enzyme inhibitor or angiotensin receptor blocker use, statin use, systolic blood pressure, fasting blood glucose, and body mass index); (3) change in estimated glomerular filtration rate (eGFR) and urine albumin-to-creatinine ratio (UACR); and (4) health outcomes (incident end-stage kidney disease [ESKD], coronary heart disease [CHD], stroke, and death). Logistic and linear regressions were used to examine the association of baseline CKD awareness with outcomes of interest, adjusted for CKD stage and participant demographic and clinical factors. Of 6,529 participants with baseline CKD, 285 (4.4%) were aware of their CKD. Among the 3,586 participants who survived until follow-up (median 9.5 years), baseline awareness was not associated with subsequent odds of health behaviors, CKD management indicators, or changes in eGFR and UACR in adjusted analyses. Baseline CKD awareness was associated with increased risk of ESKD (adjusted hazard ratio [aHR] 1.44; 95% CI 1.08-1.92) and death (aHR 1.18; 95% CI 1.00-1.39), but not with subsequent CHD or stroke, in adjusted models. Individuals aware of their CKD were more likely to experience ESKD and death, suggesting that CKD awareness reflects disease severity. Most persons with CKD, including those that are high-risk, remain unaware of their CKD. There was no evidence of associations between baseline CKD awareness and longitudinal health behaviors, CKD management indicators, or eGFR decline and albuminuria.